2006
DOI: 10.1042/bj20051595
|View full text |Cite
|
Sign up to set email alerts
|

Radical scavenger can scavenge lipid allyl radicals complexed with lipoxygenase at lower oxygen content

Abstract: Lipoxygenases have been proposed to be a possible factor that is responsible for the pathology of certain diseases, including ischaemic injury. In the peroxidation process of linoleic acid by lipoxygenase, the E,Z-linoleate allyl radical-lipoxygenase complex seems to be generated as an intermediate. In the present study, we evaluated whether E,Z-linoleate allyl radicals on the enzyme are scavenged by radical scavengers. Linoleic acid, the content of which was greater than the dissolved oxygen content, was trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
17
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 29 publications
(36 reference statements)
2
17
0
Order By: Relevance
“…We confirmed that the presence of the nitroxyl radical did not prevent the lipoxygenase reaction as follows: when 1.0 mM linoleate was incubated with 0.1 mM lipoxygenase in the presence or absence of CmDP (1.0 mM), there is no significant difference in the initial rate of hydroperoxide generation between the two systems (approximately 2.4 mM/sec). Remarkably, the nitroxyl radical scavenges the linoleate allyl radical on the ferrous lipoxygenase at lower oxygen content, resulting in the release of the inactive ferrous lipoxygenase (13). It is generally known that lipid hydroperoxides play a key role in the conversion of ferrous lipoxygenase into active ferric lipoxygenase, generating lipid alkoxyl radicals (14-16), which easily turn into epoxyallyl radicals through intramolecular rearrangement.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We confirmed that the presence of the nitroxyl radical did not prevent the lipoxygenase reaction as follows: when 1.0 mM linoleate was incubated with 0.1 mM lipoxygenase in the presence or absence of CmDP (1.0 mM), there is no significant difference in the initial rate of hydroperoxide generation between the two systems (approximately 2.4 mM/sec). Remarkably, the nitroxyl radical scavenges the linoleate allyl radical on the ferrous lipoxygenase at lower oxygen content, resulting in the release of the inactive ferrous lipoxygenase (13). It is generally known that lipid hydroperoxides play a key role in the conversion of ferrous lipoxygenase into active ferric lipoxygenase, generating lipid alkoxyl radicals (14-16), which easily turn into epoxyallyl radicals through intramolecular rearrangement.…”
Section: Resultsmentioning
confidence: 99%
“…In both cases, lipid allyl radical-CmDP adducts and lipid epoxyallyl radical-CmDP adducts were detected. The scavenging of lipid allyl radicals on the ferrous lipoxygenase by the nitroxyl radical promotes the one-electron redox cycle reaction (13).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Fig. 1, coexisting nitroxyl radical (CmDP) scavenges the FA allyl radical on the lipoxygenase, producing FA allyl radicalnitroxyl radical adducts and ferrous lipoxygenase (11). Subsequently, the ferrous lipoxygenase should be reoxidized to ferric one by cycling hydroperoxides through a pseudoperoxidase reaction, generating a FA alkoxyl radical, which may be intramolecularly rearranged by the addition of a double bond to form the FA epoxyallyl radical (carbon-centered radical) (16,17).…”
Section: Resultsmentioning
confidence: 99%
“…In our previous reports (11,12), we established a novel method for converting ferric lipoxygenase into its ferrous form. When soybean ferric lipoxygenase was incubated with PUFAs in the presence of nitroxyl radical, which selectively traps carbon-centered radicals, FA allyl radical on the ferrous lipoxygenase (13-15) was trapped by nitroxyl radical, generating ferrous lipoxygenase.…”
mentioning
confidence: 99%